Uptake of hysterectomy and bilateral salpingo-oophorectomy in carriers of pathogenic mismatch repair variants: a Prospective Lynch Syndrome Database report. (May 2021) - Seppälä, Toni T.; Dominguez-Valentin, Mev; Crosbie, Emma J.; Engel, Christoph; Aretz, Stefan; Macrae, Finlay; Winship, Ingrid; Capella, Gabriel; Thomas, Huw; Hovig, Eivind; Nielsen, Maartje; Sijmons, Rolf H.; et al.
Abstract: Purpose: This study aimed to report the uptake of hysterectomy and/or bilateral salpingo-oophorectomy (BSO) to prevent gynaecological cancers (risk-reducing surgery [RRS]) in carriers of pathogenic MMR ( path_MMR ) variants. Methods: The Prospective Lynch Syndrome Database (PLSD) was used to investigate RRS by a cross-sectional study in 2292 female path_MMR carriers aged 30–69 years. Results: Overall, 144, 79, and 517 carriers underwent risk-reducing hysterectomy, BSO, or both combined, respectively. Two-thirds of procedures before 50 years of age were combined hysterectomy and BSO, and 81% of all procedures included BSO. Risk-reducing hysterectomy was performed before age 50 years in 28%, 25%, 15%, and 9%, and BSO in 26%, 25%, 14% and 13% of path_MLH1, path_MSH2, path_MSH6, and path_PMS2 carriers, respectively. Before 50 years of age, 107 of 188 (57%) BSO and 126 of 204 (62%) hysterectomies were performed in women without any prior cancer, and only 5% (20/392) were performed simultaneously with colorectal cancer (CRC) surgery. Conclusion: Uptake of RRS before 50 years of age was low, and RRS was rarely undertaken in association with surgical treatment of CRC. Uptake of RRS aligned poorly with gene- and age-associated risk estimates for endometrial or ovarian cancer that were published recently from PLSD and did not correspond well with current clinical guidelines. The reasons should be clarified. Decision-making on opting for or against RRS and its timing should be better aligned with predicted risk and mortality for endometrial and ovarian cancer in Lynch syndrome to improve outcomes. Highlights: Premenopausal oophorectomies in patients not at increased risk of ovarian cancer. Uptake of risk-reducing surgery (RRS) in Lynch syndrome aligns poorly with cancer risk and mortality. Uptake of RRS does not correspond well with current clinical guidelines. There is an unmet need for multidisciplinary planning to avoid repeated surgery.